Associations between polymyalgia rheumatica and giant cell arteritis and 12 cardiovascular diseases. Issue 5 (19th January 2016) - Pujades-Rodriguez, Mar; Duyx, Bram; Thomas, Sara L; Stogiannis, Dimitris; Smeeth, Liam; Hemingway, Harry
Abstract : Objectives: Evidence of the association of polymyalgia rheumatica (PMR) and giant cell arteritis (GCA) with the full range of cardiovascular diseases (CVDs) is limited. We examined their relationship with the first clinical presentation of the 12 most common CVDs in an unselected population-based cohort of men and women. Methods: We analysed CArdiovascular disease research using LInked Bespoke studies and Electronic health Records (CALIBER) data, which links primary care and hospital and mortality data in England, from 1997 to 2010. We assembled a cohort of men and women initially free from CVD at baseline and included all patients with PMR and/or GCA (PMR/GCA) diagnosis, matched by age, sex and general practice with up to 10 individuals without PMR/GCA. Random effects Poisson regression analysis was used to study the association between PMR/GCA and the initial presentation of 12 types of CVDs. Results: The analysis included 9776 patients with PMR only, 1164 with GCA only, 627 with PMR and GCA and 105 504 without either condition. During a median of 3.14 years of follow-up 2787 (24.1%) individuals with PMR/GCA and 21 559 (20.4%) without PMR/GCA developed CVDs. Patients with PMR/GCA had lower rates of unheralded coronary death (3.18 vs 3.61/1000 person-years; adjusted incidence ratio 0.79, 95% CI 0.66 to 0.95), transient ischaemic attack (5.11 vs 5.61/1000 person-years; 0.67, 95% CI 0.54 to 0.84) and coronary and death composite (24.17 vs 25.80/1000 person-years; 0.90, 95% CI 0.82 to 0.98). No associations were observed for other CVDs or cerebrovascular diseases, and in patients with only PMR or GCA. No evidence of interaction by age or sex was found. Estimates decreased with longer PMR/GCA duration and findings were robust to multiple sensitivity analyses. Conclusions: In this large contemporary population-based cohort the presence of PMR and/or GCA was not associated with an increased risk of CVDs or cerebrovascular diseases regardless of PMR/GCA duration.